PENINGKATAN HASIL BELAJAR IPS MELALUI MODEL PEMBELAJARAN ROLE PLAYING PADA SISWA KELAS V SD INPRES TELLO BARU II KOTA MAKASSAR - Syamsuddin , Syamsinar; Yunus, Muhammad; Hamid, Sundari (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2020)
The aim of this study was the result of social studies material Severe Resistance fighters’ figure at the Dutch occupation and Japan through a model of the student clear Role-Playing V SD Instruction New Tello penilitian II study is a class act. The data collection technique used is the technique tests and observation. The subjects were students of class V SD Instruction New Tello II Makassar with the number of 30 students. Severe Struggle IPS learning research Figures Warriors on Dutch colonization and Japanese students showed good after the second cycle based on problems experienced by students in cycle I. It is proved from the first cycle, namely that scored above 85 to as many as 4 people or 13.33 %. While the number of students who reach a value of less than as many as 26 people or 86.66%. While on the second cycle, there is an increase showed that the number of students achieving top grades 85 to 21 persons, or 70%. While the number of students who reach a value of less than 85% that is 9 or 30%. Therefore, it can be concluded that the ability of learning outcomes Severe Leaders Struggle material fighters in Dutch and Japanese colonization in Class V SD Instruction New Tello II was increased after the applied model of role playing.